The cream formula on winter solstice - Zhang Ruqing (Wolters Kluwer Health/LWW, 2018)
This study introduces the application of cream formula in Traditional Chinese medicine. When the phase of Yin extremity comes, yang qi starts to generate itself. Winter solstice is the optimum period for the application of cream formula. Formula refers to the thick liquid further simmered from medical decoction to benefit and nourish the human body and rectify imbalance to cure diseases, which can achieve excellent effect on not only health preservation, body strengthening, and sub-optimal conditioning but also recuperative care of chronic diseases.